PENGARUH IRADIASI BERKAS ELEKTRON TERHADAP ASAM-ASAM ORGANIK, ASAM AMINO DAN ANALISIS PROKSIMAT JAMUR KUPING (Auricularia auricula) KERING (Irradiation Effect of Electron Beams on Organic Acids, Amino Acids and Proximate Analysis of Dried Ear Fungus (Auri - Kadir, Idrus; Darwis, Darmawan (Baristand Industri Banda Aceh, 2016)
Has been conducted research on the effects of electron beam irradiation on organic acids,amino acids and proximate analysis of dried ear mushroom (Auricularia auricula). Ear Mushroom is a typeof edible mushroom which is very popular with consumers, therefore, post-harvest handling in the form ofdried mushrooms is very important to maintain an economical agribusiness chain. Handling of driedmushroom with electron beam irradiation was performed. The purpose of this study was to determine theeffect of electron beam irradiation at a dose of 5 kGy to the content of organic acids (acid of propionate,acetate, butyrate, citrate, lactate, and oxalic acid) and proximate analysis of dried mushroom. The resultsshowed that irradiation at 5 kGy increase the content of citric acid and oxalic acid significantly lowered.While on amino acid and proximate analysis (moisture, fat, protein, and carbohydrates) as well as pH,water activity (aw) and density of dried mushroom, irradiation at a dose of 5 kGy relatively not change thevalue of amino acid as well as proximate analysis value as well as pH, aw and density of the fungus.